Eating dinner away from home: Perspectives of middle-to high-income parents. (1st January 2016) - Robson, Shannon M.; Crosby, Lori E.; Stark, Lori J.
Abstract: This study sought to understand barriers and facilitators for preparing and eating dinner at home in families who report eating dinner away from home ≥3 times per week. Cross-sectional, mixed methods (focus groups, questionnaires) study. Twenty-seven parents with a child 3–10 years-old who reported eating dinner away from home ≥3 times per week from a pediatric medical center in the Midwest participated. The key concepts analytic framework guided focus group analysis. Descriptive statistics were used to characterize parent demographics, anthropometrics, attitudes and confidence toward cooking, perceptions of dinner costs and portions, and parent and child dinners. Parents reported confidence in cooking a home prepared meal, but that eating away from home was reinforcing because it provided quality family time and diminished barriers such as picky eating and perceived costs. Home cooking was also hindered by early school lunch and after-school sports as children were not hungry or home at the typical dinner hour and parents did not want to cook after 8pm. Parents estimated preparing and eating a meal at home took significantly more time than driving and eating out (80.7 min vs. 30.3 min, p < 0.001). Parents significantly (F (3, 104) = 8.80, p < 0.001) overestimated the cost of home-prepared meals compared to take-out and frozen meals. Portion size was also overestimated for a protein serving. Findings are limited to predominantly married, female parents whom are highly educated and working. To reduce eating out, interventions should address family factors (e.g., time management, quality time) and child behavior (e.g., picky eating). Innovative interventions that include experiential cooking opportunities that incorporate time management, address picky eating and enthusiasm for cooking with education on decreasing costs may be particularly beneficial for middle-to high-income families. Highlights: Focus groups with affluent parents who reported eating away from home often. Societal factors, cost, and parent expectations of meal times influence eating out. Competing priorities with preparing food at home may differ by income-status. Interventions need to address time management and child eating behavior.